Teachers' innovativeness and teaching approach: The mediating role of creative classroom behaviors - Ucuş, Şükran; Acar, İbrahim Hakkı (Scientific Journal Publishers, 2018)
We examined the associations between teachers' innovativeness, creative classroom behaviors, and teaching approach (constructivist and traditional) focusing in particular, on the mediating role of teachers' creative classroom behaviors in the relationship between their innovativeness and their teaching approach. We recruited 247 teachers (80.6% women, 19.4% men) working in early childhood centers and junior classes at elementary schools in Turkey to participate in the study. Participants reported on their innovativeness, creative classroom behaviors, and teaching approach. There was a positive association between creative classroom behaviors and use of the constructivist teaching approach, and a negative association between innovativeness and use of the traditional teaching approach. Mediation analysis results showed that there was an indirect effect from innovativeness to the constructivist teaching approach through creative classroom behaviors but this effect did not occur when a traditional teaching approach was used. Implications of our findings are discussed.
WOS: 000447028500010
Keywords: Creative Classroom Behavior; Teacher Innovativeness; Teaching Approach; Innovation; Turkish Education System